Implementing Project-Based Learning: Effects on EFL Students' Language Acquisition and Engagement - Sadad, Anwar; Juhana, Juhana; Saehu, Andang (SCOPE: Journal of English Language Teaching, 2024)
This qualitative case study explores the implementation of Project-Based Learning (PBL) stages by an English teacher to enhance language acquisition among young learners in an Indonesian elementary school. The research examines the specific PBL stages employed and investigates students' perceptions of these stages in relation to their English language development. Classroom observations, semi-structured interviews, and document analysis were used to collect data from the participating teacher and students. The findings reveal that the teacher implemented a four-stage PBL approach: Starting the Project, Developing the Project, Reporting to the Class, and Assessing the Project. Each stage incorporated key PBL principles such as student autonomy, authentic tasks, scaffolding, and ongoing assessment. Students expressed positive perceptions of the PBL stages, highlighting benefits such as clear project introduction, engaging research activities, valuable teacher feedback, and peer collaboration. They also reported increased motivation to use English due to the teacher's encouragement, personal interest, and the project's engaging nature. Although, some viewed English use as merely a project requirement. The study concludes that the PBL stages implemented by the teacher positively enhanced students' English language learning. The findings contribute to the understanding of PBL implementation in EFL contexts, providing insights into young learners' experiences with this approach and highlighting the potential of PBL to enhance language skills and engagement. Simultaneously, the study identifies areas for improvement in PBL implementation, offering valuable guidance for educators seeking to optimize this approach in their classrooms.